Treatment of high strength organic wastewater by using an anaerobic membrane bioreactor - Wonglertarak, Watcharapol; Wichitsathian, Boonchai; Boonyungyuen, Wimonmas; Te, Borano (Asia-Pacific Journal of Science and Technology, 2024)
Properly managing wastewater with high concentrations of organic compounds is essential to prevent adverse environmental impacts. This study several various values of hydraulic retention times (HRT) to determine the optimal conditions for an anaerobic membrane bioreactor (AnMBR), as well as its performance and membrane fouling. The results indicated that an optimal chemical oxygen demand (COD) removal efficiency of 81.18% was achieved for a 48-hour HRT condition. The organic removal rate (ORR) was found to be 7.90 kg COD/m3-day, with biogas productivity of 0.224 m3/kg CODremoved. The potential operation was optimal for the 48-hour HRT condition compared to the other conditions. Importantly, the study revealed that a longer HRT could mitigate membrane fouling in the AnMBR, which was attributed to the impact of the volumetric organic loading rate.